A Simulation on the Effect of Ultrasonic Vibration on Ultrasonic Assisted Soldering of Cu/SAC305/Cu Joint - Abdul Jalil, Nawal Aswan; Kadhim Sharaf, Hussein; Salman, Sadeq (Journal of Advanced Research in Applied Mechanics, 2020)
In the modern electronic packaging industry, the trend of miniaturization and the demand for advanced features of electronic devices have greatly reduced the size and weight of the electronic packages but increased the density of the packaging system. Higher input/output current density has to flow through these miniature interconnects or solder joints within the packaging system and thus, causing heat generated by the system to increase tremendously. This has driven the packaging design to include a built-in thermal enhancement feature, such as a large area bottom metal or heat sink to provide a direct thermal path out from the package to ease heat dissipation. So the main objectives of this study are to valid experimental work for solder joint failure due to the ultrasonic vibration and to investigate better mechanical properties for solder joint by FE analysis. ANSYS software has been used to analysis boundary conditions with the assistance of design modular (DM) to produce the model then export the model to ANSYS. After that input boundary conditions, the output of the simulation is shear stress then compare shear stress of experimental work with the output of the simulation. From the finding of 87% comparison between simulation to experimental work so will continue to try new parameters with same boundary conditions. It is showed that the maximum shear strength is 55 MPa for Cu/SAC305/Cu when it treated with 50 kHz for 4.5 sec and minimum shear strength is 35 MPa when it treated with 70 kHz at control time (0 sec). finally, this study discovered that the best method to improve mechanical properties for Cu/SAC305/Cu solder alloy treat this solder joint with frequency 50 kHz for 4.5 sec to get maximum shear strength.